Stereocomplexation of Poly(Lactic Acid)s on Graphite Nanoplatelets: From Functionalized Nanoparticles to Self-assembled Nanostructures - Eleuteri, Matteo; Bernal, Mar; Milanesio, Marco; Monticelli, Orietta; Fina, Alberto (Frontiers in Chemistry, 2019)
The control of nanostructuration of graphene and graphene related materials (GRM) into self-assembled structures is strictly related to the nanoflakes chemical functionalization, which may be obtained via covalent grafting of non-covalent interactions, mostly exploiting π-stacking. As the non-covalent functionalization does not affect the sp2 carbon structure, this is often exploited to preserve the thermal and electrical properties of the GRM and it is a well-known route to tailor the interaction between GRM and organic media. In this work, non-covalent functionalization of graphite nanoplatelets (GnP) was carried out with ad-hoc synthesized pyrene-terminated oligomers of polylactic acid (PLA), aiming at the modification of GnP nanopapers thermal properties. PLA was selected based on the possibility to self-assemble in crystalline domains via stereocomplexation of complementary poly(L-lactide) (PLLA) and poly(D-lactide) (PDLA) enantiomers. Pyrene-initiated PLLA and PDLA were indeed demonstrated to anchor to the GnP surface. Calorimetric and X-ray diffraction investigations highlighted the enantiomeric PLAs adsorbed on the surface of the nanoplatelets self-organize to produce highly crystalline stereocomplex domains. Most importantly, PLLA/PDLA stereocomplexation delivered a significantly higher efficiency in nanopapers heat transfer, in particular through the thickness of the nanopaper. This is explained by a thermal bridging effect of crystalline domains between overlapped GnP, promoting heat transfer across the nanoparticles contacts. This work demonstrates the possibility to enhance the physical properties of contacts within a percolating network of GRM via the self-assembly of macromolecules and opens a new way for the engineering of GRM-based nanostructures.